OFF-THE-SHELF COOK® T-BRANCH® BRANCHED ENDOPROSTHESIS DEPLOYMENT: TECHNICAL ASPECTS AND TIPS AND TRICKS - Lopes, Alice Cabral (2021)
Introduction: Off-the-shelf multi-branched stent grafts, such as Cook t-Branch®, emerged as an alternative for the prompt treatment of thoracoabdominal aneurysms (ATA). Objective/Technique: In our institution, the use of the Cook T-Branch® stent graft has been carried out in urgent cases and in some elective cases with favorable anatomy and in which it is not advisable to wait for the production of a custom-made device (CMD). The accumulated experience justifies the purpose of this review article, which aims to describe the deployment, some adjuvant techniques and some tips and tricks that may facilitate the learning curve in centers with less contact with this platform. Conclusion: The use of off-the-shelf multi-branched stent grafts, such as Cook T-Branch®, is a safe and viable alternative for the treatment of ATA. The main advantage of this approach is its prompt accessibility. As we advance in the learning curve and new adjuvant techniques are acquired, their applicability is significantly increased, both in the urgent and elective context.